Christian intellectuals and the Roman Empire from Justin Martyr to Origen - Secord, Jared (Inventing Christianity., 2020)
"A novel treatment of a group of early Christian authors, demonstrating that their behavior and self-presentation were shaped by the norms of Roman intellectual culture, and not simply by factors internal to Christianity." -- Provided by publisher.